The Association Between Pleural Empyema and Peripheral Arterial Disease in Younger Patients: A Retrospective National Population-Based Cohort Study - Wang, Tzu-Yuan; Chen, Hsin-Hung; Su, Chun-Hung; Hsu, Sheng-Pang; Ho, Chun-Wei; Hsieh, Ming-Chia; Lin, Cheng-Li; Kao, Chia-Hung (Frontiers in Medicine, 2021)
Background: To investigate the relationship between pleural empyema (PE) and peripheral arterial disease (PAD). Methods: We conducted a retrospective cohort study using data from the National Health Institute Research Database. Univariable and multivariable Cox's proportional hazard regressions were performed to investigate the association between PE and the risk of PAD. Kaplan–Meier method and the differences were assessed using a log-rank test. Results: The overall incidence of PAD was higher in the PE cohort than in the non-PE cohort (2.76 vs. 1.72 per 1,000 person-years) with a crude hazard ratio (HR) of 1.61 [95% confidence interval (CI) = 1.41–1.83]. After adjustment for age, gender, and comorbidities, patients with PE were noted to be associated with an increased risk of PAD compared with those without PE [adjusted HR (aHR) = 1.18, 95% CI = 1.03–1.35]. Regarding the age-specific comparison between the PE and non-PE cohorts, PAD was noted to be significantly high in the ≤ 49 years age group (aHR = 5.34, 95% CI = 2.34–10.1). The incidence of PAD was higher in the first 2 years, with an aHR of 1.35 (95% CI = 1.09–1.68) for patients with PE compared with those without PE. Conclusion: The risk of PAD was higher if patients with PE were younger than 49 years and within the 2-year diagnosis of PE.